Development of the model of forces and resources coordination in hierarchical system of civil protection - Ляшенко, Елена Николаевна; Шерстюк, Владимир Григорьевич (Technology audit and production reserves, 2015)
The paper deals with a hierarchical management structure in the system of civil protection of the population and the peculiarities of the Coordinating control of the system. It is shown that the hierarchical system of civil protection of the population belongs to a class of semi-complex dynamic systems. Task coordination in this class is intractable and cannot be solved using classical approaches. Therefore, in this paper, we proposed to reduce the problem of the coordination of the civil protection of the population to the problem of support for targeted co-operative decision-making. The features of the tasks of coordination are considered, subtasks of coordinate decisions and coordinate actions are formulated, implicit and explicit forms of coordination are highlighted. It is conducted four-level decomposition of management structure that allowed developing the multi-agent model with the regulatory control. The principles of coordination in the hierarchical system of civil protection, implementation of which will develop mechanisms for coordination and synchronization of the objectives, plans and actions of governments at various levels of the hierarchy are proposed It is shown that implicit coordination on the basis of the proposed model can be achieved through the mechanism of a joint search for solutions to the agents, and a clear coordination - through the mechanism of coordination of plans agents. It is proposed to solve subtask coordination in the planning of the activity of agents and sub-task coordination - in the process of implementation of the plans, dynamically adjusting them under the influence of external disturbances. The implementation of proposed in this paper mechanisms for solving subtasks of coordinate decisions and actions in the explicit and implicit forms in the multi-agent model of a hierarchical system with a standard controller allows to find the solution of the urgent task of coordinating the forces and means in a hierarchical system of civil protection. The results of this work can be used to create decision support systems in emergencies.